Meta-Analysis of the Effect of Internet-Based Self- Management on Blood Glucose Control in Type 2 Diabetes Mellitus Patients - Maulana, Moh; Tamtomo, Didik; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder or disease with numerous etiologies characterized by high blood glucose levels accompanied by lipid, protein, and carbohydrate metabolism disorders. Type 2 diabetes is the most common type of diabetes with about 90% of all diabetes cases. The International Diabetes Federation (IDF) estimates that the number of diabetics in the world can reach 783.7 million people while in Indonesia it is estimated to reach 28.57 million people in 2045. This number is an increase of 46% compared to 536.6 million in 2021. The study aims to discover how much influence internet-based self-management has on blood glucose control in type-2 diabetes mellitus patients.Subjects and Method: It was a meta-analysis study using PRISMA flowchart guidelines with the PICO formulation. P = type 2 diabetes mellitus patients. I = Internet-based self-management. C= No internet-based self-management. O= HbA1C. This study was conducted by searching for articles obtained from the MEDLINE/PubMed, Google Scholar, ProQuest, Science Direct, and Spinger Link databases with keywords and operators “Boolean electronic health record